Toxic Work Culture and Power Imbalance: A Qualitative Psychososial Study In the Contact Center Industry - Prasetyo, Eko Agus; Handayani, Fitria; Anisa; Mahpur, Mohammad (Faculty of Psychology, Universitas Semarang, 2025)
Toxic work culture has become a major concern in organizational psychology due to its impact on mental health and productivity. This study explores how power imbalances, weak organizational systems, and the absence of protective mechanisms create psychosocial stress in the workplace. Using a qualitative case study in the Contact Center Industry in Central Java and Yogyakarta, 10 participants from various job levels were interviewed through semi-structured interviews, observations, and document analysis. Data were analyzed using thematic coding. Findings revealed three dominant themes: psychological insecurity (63%), reflected in withdrawal, fear of speaking up, and loss of initiative; toxic behaviors (18%), such as sarcasm and verbal abuse tolerated due to high performance; and structural dysfunction (23%), including the absence of conflict SOPs and weak HR intervention. Employees responded with self-protection strategies like social withdrawal. This study contributes to developing ethical and psychologically safe organizational systems through ethics-based evaluation and stronger HR functions.